2015
DOI: 10.1021/acs.cgd.5b00096
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Growth Twinning and Crystalline Reorientation of Faceted Growth Materials during Directional Solidification

Abstract: The correlation between growth twinning and crystalline reorientation of faceted growth materials during directional solidification was demonstrated through matrix calculation and Thompson regular tetrahedron model diagrams. The correlation is that the crystalline reorientation results from the mirror symmetry operation of initial orientation on different twin planes. In total, seven possibilities of crystalline reorientation caused by single-twinning from ⟨110⟩, ⟨111⟩, and ⟨112⟩ initial axial orientation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The correct T matrices should be the ones for the misorientation axis/angle pair of ⟨1̅ 10⟩/70.5°, which was observed in the experiment. 13 On the other hand, in the method mentioned in ref 12 which we adopted, the growth orientation (column vector) of the…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The correct T matrices should be the ones for the misorientation axis/angle pair of ⟨1̅ 10⟩/70.5°, which was observed in the experiment. 13 On the other hand, in the method mentioned in ref 12 which we adopted, the growth orientation (column vector) of the…”
Section: Discussionsupporting
confidence: 82%
“…Fortunately, the transformation matrix (T matrix) is a useful tool for the analysis, because it focuses on the orientation relationship instead of the structural one. The use of the mirror symmetric operation for T matrices was reported recently, 12,13 but still some experimental results could not be explained by the proposed T matrices. Because the previous matrices were calculated based on the two grains being misoriented by 180°, they were not sufficient at all.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the transformation of the preferred axial orientation was explained by the different space-occupying capacities caused by the different morphological configurations for <101> and <112> axially oriented grains [24]. The growth twins of Tb-Dy-Fe alloys changed the crystal orientation, which was related to the crystal orientation of mirror symmetry [22]. Previous studies have shown that different solidification rates correspond to different solidification morphologies; that is, with the increase in the solidification rate, the preferred axial orientation changed from <101> to <112> and was then reoriented to <101> [23].…”
Section: Grain Growth and Orientation Control During Directional Soli...mentioning
confidence: 99%
“…Therefore, an in-depth understanding of directional solidification of the (Tb,Dy)Fe 2 intermetallic is the topic of interest with a special emphasis on orientation selection and microstructural evolution. Several researchers, including the authors, [4][5][6][7][8][9][10][11][12][13][14][15] are pursuing investigations in this area, and the efforts have led to an improved know-how of the physical metallurgical aspects of this material. However, the key issue that remains unresolved is to grow the material successfully with h111i texture.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, zone melting or modified Bridgman techniques offer scope for obtaining specimens of larger dimensions. Although reports on formation of different texture components through these methods are available, [4][5][6][7][8][9][10][11][12][13][14][15] an integrated theory on the underlying mechanism is yet to evolve that can explain the orientation selection as a function of solidification parameters.…”
Section: Introductionmentioning
confidence: 99%